ANALISIS PENGARUH EXPERIENTIAL MARKETING TERHADAP LOYALITAS MELALUI KEPUASAN NASABAH SEBAGAI VARIABEL INTERVENING - Fatmawati, Ratna Dian; Rahayu, Yayuk Sri (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan; Vol 1 No 1 (2018): Prosiding Seminar Nasional dan Call for Papers Manajemen, Akuntansi, dan Perbankan 2018, 2018)
The purposes of this research are to know the influence of experiential marketing to customer loyalty through customer satisfaction.The research used quantitative approach with descriptive type. The sample of the research was108customersof BRISyariahMalang using simple random sampling method. The data analysis used path analysis.The research resultshows that experiential marketing consist of sense, feel, act, relate influenced significant and positivetocustomer satisfaction, the variable of think had a significant negative influence tocustomer satisfaction. Experiential marketing consist of the variables sense, feel, act, relate influenced significant and positiveto customer loyalty, the variable of think had a significant negative influence to customer loyalty. The customer satisfaction had a positive influence to customer loyalty. Finally, experiential marketing influenced to loyalty through customer satisfaction